Unwed and Unheard: Structural Constraints and Cultural Pressures Facing Economically Vulnerable Women in Kashmir, India - Asif Bashir; Naseer Ahmad Bhat; Tasleema Akhter (RADJA PUBLIKA, 2025)
This study critically interrogates the socio-cultural and economic determinants underpinning the phenomenon of late and non-marriage among women above the age of 40 in the Kashmir Valley. Drawing on primary data collected from 108 unmarried women engaged in low-income occupations such as homemaking, private tuition, and informal sector work, the research elucidates how entrenched cultural expectations particularly the prevalence of dowry demands and the social compulsion for extravagant wedding expenditures conspire with financial precarity to delay or entirely obstruct marriage prospects. The analysis employs both descriptive statistics and chi-square testing to establish significant correlations between occupational status and the reasons cited for remaining unmarried, revealing that women’s economic contributions often fail to mitigate the barriers imposed by patriarchal traditions and materialist social norms. Further, the study problematizes the socio-psychological implications of prolonged singleness, situating these women within a matrix of marginalization marked by emotional distress, familial burden, and diminished social visibility. Remedies proposed encompass structural reforms, legal enforcement against dowry, targeted marriage support schemes, vocational empowerment, and a reconceptualization of societal narratives around marriage and womanhood. The study concludes that without a multidimensional recalibration of both policy and cultural ethos, the marital exclusion of economically vulnerable women will persist, perpetuating cycles of gendered inequality and social alienation.